Social Resilience Strategies Through Community-Based Tourism In The Era Of New Habits Adaptation - Luthfitah, Rifdah; ., Suryoto; ., Ranjani (KnE Social Sciences, 2023)
Indonesia is one of many nations whose economies have been crippled by the COVID- 19 outbreak. The reduction in per capita income, which has an effect on the community’s social resilience, is directly impacted by COVID-19. Through community-based tourism, this study intends to identify the social resilience strategy in Banyumas District, Banyumas Regency, in the age of habit adaption. In-depth interviews, documentation, and observation are the three methods of data collection using qualitative approaches. The study’s findings suggest that the COVID-19 pandemic is to blame for a region’s declining socioeconomic resilience, particularly for the welfare of those who depend on the tourism industry. The Banyumas District government’s ”Peken Banyumasan” community-based tourism initiative is employed as a tactic to sustain socioeconomic resilience in Banyumas District, Banyumas Regency. Community-based tourism has not yet completely realized its potential. This is a result of Ketenger Village’s lack of community involvement and the Regional Government’s dominance as the event organizer and planner. Keywords: covid-19, community-based tourism, social resilience